Histopathologic approach to cutaneous vasculitis - Rajalakshmi Tirumalae (Wolters Kluwer Medknow Publications, 2014)
Cutaneous vasculitis encompasses a varied clinicopathologic spectrum, some of them with grave systemic consequences. A skin biopsy is often part of the first-line investigations done in the workup of such patients. A pathologist confronted with a biopsy for vasculitis has to be cognisant of the variations in morphology of these lesions with the course of the disease, overlaps in clinical and histologic features, use of ancillary tests like direct immunofluorescence (DIF), and its limitations. This review outlines a practical histopathologic approach to cutaneous vasculitis and emphasizes features that help in differential diagnosis.